1999
DOI: 10.1002/(sici)1099-0682(199908)1999:8<1271::aid-ejic1271>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Predetermined Chirality in Mono- and Dinuclear Cyclometalated Rhodium(III) Complexes

Abstract: Dinuclear and polynuclear metal complexes with octahedral eluent contains NaCl. Modeling the ΛΛ and the ∆Λ isomers of the dinuclear species shows crowding of the pinene centers coordinated to di-or polydentate ligands are often obtained as complicated mixtures of various stereoisomers. groups in both cases; however, the strain can be released by relatively small distortions only in the case of the ΛΛ isomer. Stereospecific synthesis of such species is therefore of high current interest. Chiral derivatives of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…The chloride ligands reside in the equatorial plane trans to the fppy C atoms and the fppy N atoms occupy the apical sites with trans geometry. This is consistent with other dinuclear iridium(III) and rhodium(III) complexes of this type (Fronczek et al, 1982;Steel, 1991;Garces et al, 1993;Ghisdavu et al, 1999). However, the IrÐCl bond lengths fall into two groups, differing by approximately 0.1 A Ê , with both IrÐCl1 bonds shorter than the IrÐCl2 bonds (Table 1).…”
Section: Commentsupporting
confidence: 89%
“…The chloride ligands reside in the equatorial plane trans to the fppy C atoms and the fppy N atoms occupy the apical sites with trans geometry. This is consistent with other dinuclear iridium(III) and rhodium(III) complexes of this type (Fronczek et al, 1982;Steel, 1991;Garces et al, 1993;Ghisdavu et al, 1999). However, the IrÐCl bond lengths fall into two groups, differing by approximately 0.1 A Ê , with both IrÐCl1 bonds shorter than the IrÐCl2 bonds (Table 1).…”
Section: Commentsupporting
confidence: 89%
“…This phenomenon has also been observed in bridged dinuclear octahedral complexes using suitable chiral building blocks in the solid state 2a,2b,4. A pronounced diastereoselectivity was reported in dinuclear ΔΔ[Rh(L) 2 (μ‐Cl)] 2 [L = th4,5( R , R )ppy] with ΔΔ/ΛΛ = 9:1 and in ΛΛ[Rh(L′) 2 (μ‐Cl)] 2 [L′ = th4,5( S , S )ppy] with ΛΛ/ΔΔ = 9:1, according to the results of X‐ray studies 17a…”
Section: Introductionmentioning
confidence: 86%
“…The homochiral complexes are energetically favoured by 7.77 kcal/mol at HartreeϪFock level. On the basis of molecular modelling studies of [(ppy) 2 Rh(µ-Cl)] 2 [19] and closely related complexes, [20] it has previously been suggested that the meso form is less stable due to interligand steric repulsion. Accordingly, for this class of compounds only ∆∆/ΛΛ complexes have been structurally characterized.…”
Section: Computational Studymentioning
confidence: 99%
“…Accordingly, for this class of compounds only ∆∆/ΛΛ complexes have been structurally characterized. [20,21] A common feature of all the symmetrical complexes is a planar M(µ-Cl) 2 M unit (Table 2, Entries 1Ϫ11), the only exception being [(PPh 3 ) 2 Pd(µ-Cl)] 2 2ϩ , which displays a slightly bent chloro bridge in the crystal. This characteristic is also observed for most other halo-bridged complexes of d 8 transition metal ions.…”
Section: Computational Studymentioning
confidence: 99%